Being Enclosed as a Lifestyle: Complex Neolithic Settlements of Eastern Croatia Re-Evaluated through Aerial and Magnetic Survey - Hrvoje Kalafatić; Rajna Šošić Klindžić; Bartul Šiljeg (Geosciences, 2020)
Archeological excavations and field survey of Neolithic sites during the last 100 years have formed a certain framework within which we developed an interpretation of Neolithic life in this area. Even though researchers have stressed the importance of sites, region, or period in their publications, most of the results revealed very modest remains of Neolithic settlements, too small or too scarce to provide insight in settlement size, organization, and other aspects of life. A combination of non-destructive methods of research is proving to be a more effective means of Neolithic site detection and interpretation. Here, we present the sites Gorjani-Kremenjača, Koritna-Pašnik, Gat-Svetošnice, Ivanovac-Korođvar, Klisa-Groblje, and Brdo, whose size and shape were defined through a combination of the analysis of aerial and satellite imagery and geomagnetic survey. Experience in combined research strategies will help us in our efforts to define parameters in recognizing regularities in the remains of settlement organization visible only from the air. Our results showed a complex network of densely populated settlements with elaborate internal organization and infrastructure varying in size from 10 to 50 ha. All settlements were surrounded by at least one set of ditches. Their internal organization was complex and suggests dense habitation. Many sites have several ditched spaces organized in complex systems. Obtained data and results provide a comprehensive review in a wider European context.